Shadows of the Internet: how anonymity affects the psychological health of adolescents - Bazarov, R.I. (Bulletin of Practical Psychology of Education, 2025)
Context and relevance. In the context of rapid digitalization of society, the problem of anonymity on the Internet is especially relevant for adolescents. Modern adolescents actively use anonymous digital platforms, which on the one hand opens new opportunities for self-expression and search for support, and on the other hand is associated with risks for mental health, including cyberbullying, Internet addiction and reduction of psychological tension. The relevance of the study has led to the need for a comprehensive analysis of the impact of digital anonymity on the mental health of adolescents in order to develop methods for prevention and education. Objective. The purpose of this study is to analyze the impact of digital anonymity on the psychological state and social behavior of adolescents and to identify risk factors and resources associated with anonymous online interactions. Hypothesis. It is hypothesized that online anonymity acts as both a risk factor for adolescents' mental health and a resource for personal development, given certain conditions of support and digital literacy. Methods and materials. The paper provides a review of domestic and foreign scientific publications on digital anonymity and its impact on adolescents. Empirical and theoretical studies covering the issues of cyberbullying, Internet addiction, identity formation, as well as psychological and pedagogical aspects of ensuring the safety of adolescents in the digital environment were analyzed. Results. The review showed that digital anonymity leads to the risk of anxiety, depression, aggressive and deviant behavior, and promotes cyberbullying and Internet addiction among adolescents. However, anonymous platforms can serve a psychosocial support function by providing self-expression and positive identity formation, especially when digital literacy and adult support functions are in place. Conclusions. The findings suggest the need for a comprehensive approach to preventing the effects of digital anonymity. It is important to develop adolescents' critical thinking skills, digital literacy and responsible online behavior, and to provide psychological support to minimize risk and discover the positive potential of anonymous digital media. Контекст и актуальность. В условиях быстрой цифровизации общества проблема анонимности в Интернете является особенно актуальной для подростковой среды. Современные подростки активно используют анонимные цифровые платформы, что, с одной стороны, предоставляет новые возможности для самовыражения и поиска поддержки, а с другой - связано с рисками для психического здоровья, включая кибербуллинг, интернет-зависимость и повышение психологического напряжения. Актуальность исследования обусловлена необходимостью комплексного анализа влияния цифровой анонимности на психологическое здоровье подростков для разработки методов профилактики и просвещения. Целью настоящего исследования является анализ влияния цифровой анонимности на психологическое состояние и социальное поведение подростков, а также определение факторов риска и ресурсов, связанных с анонимным онлайн-взаимодействием. Гипотеза. Предполагается, что анонимность в Интернете выступает одновременно фактором риска для психического здоровья подростков, а также ресурсом для личностного развития при наличии определенных условий поддержки и цифровой грамотности. Методы и материалы. В работе проведен обзор отечественных и зарубежных научных публикаций, посвященных цифровой анонимности и ее влиянию на подростков. Проанализированы эмпирические и теоретические исследования, охватывающие вопросы кибербуллинга, интернет-зависимости, формирования идентичности, а также психолого-педагогические аспекты обеспечения безопасности подростков в цифровой среде. Результаты. Обзор показал, что цифровая анонимность приводит к риску возникновения тревожности, депрессии, агрессивного и девиантного поведения, а также способствует распространению кибербуллинга и интернет-зависимости среди подростков. Вместе с тем анонимные платформы могут выполнять функцию психологической поддержки, обеспечивая самовыражение и формирование позитивной идентичности, особенно при наличии функций цифровой грамотности и поддержки со стороны взрослых. Выводы. Полученные результаты свидетельствуют о необходимости комплексного подхода к предотвращению последствий цифровой анонимности. Важно развивать у подростков навыки критического мышления, цифровой грамотности и ответственного поведения в сети, а также обеспечивать психологическую поддержку для минимизации риска и открытия позитивного потенциала анонимных цифровых средств.